Integrated Diagnostic Approach Using Basophil Activation Test and IgE Assays for Shrimp and Prawn Allergy - Nhu N. Q. Nguyen; Thao H. Nguyen; Minh K. Le; Tram B. Duong; Duy L. Pham; Tai T. Tran; Tu H. K. Trinh (Medicina, 2025)
Background and Objectives: Shellfish allergies are common in Vietnam. The basophil activation test (BAT) is a powerful tool in the diagnosis of food allergies. We aimed to evaluate the application of BAT to distinguish shrimp allergy in comparison with skin prick test and specific IgE measurement. Materials and Methods: We recruited adult shrimp- or prawn-allergic subjects from the University Medical Center (Vietnam). BAT was performed using the in-house crude extracts for two allergens: black tiger shrimp Penaeus monodon (shrimp) and giant freshwater prawn Macrobrachium rosenbergii (prawn). The percentages of CD63 in response to shrimp and prawn were recorded. The results of skin prick tests (SPT) and the specific IgE (sIgE) levels in response to commercial shrimp/prawn were noted. Receiver operating characteristic (ROC) analysis and area under the curve (AUC) were calculated. Results: Of 43 recruited subjects, 9 (26.5%) subjects had a specific allergy to shrimp, 2 (5.9%) subjects had a specific allergy to prawn, and 23 (67.6%) subjects had both shrimp and prawn allergy. Basophil CD63% was significantly increased in subjects with allergy to shrimp and prawn (p < 0.05% for all). Compared with SPT and sIgE, CD63 expression-based BAT was better in discriminating subjects with allergies to these species from their non-allergic counterparts (AUC/sensitivity/specificity = 0.88/77%/89% for shrimp, and 0.74/88%/77% for prawn, p < 0.05 for all). The addition of SPT and BAT improved the diagnostic power. A positive BAT could help identify shrimp/prawn allergy among cases with negative SPT/sIgE to shrimp/prawn. BAT facilitated the diagnosis of shrimp allergy among prawn-allergic subjects (100% accurate). Conclusions: The BAT test can help predict clinical reactions to shrimp and prawn in allergic patients, and enhance diagnostic accuracy in cases where SPT or specific IgE tests yield negative results.